Model studies of chlorophyll fluorescence reabsorption at chloroplast level under different exciting conditions - Naus, J; Klinkovsky, T; Ilik, P; Cikanek, D (Photosynthesis research, 1994)
A theoretical model is presented describing the distortion of chlorophyll fluorescence spectra of a chloroplast or a group of chloroplasts by the effect of fluorescence reabsorption. Model calculations using the experimental data show that the primary reabsorption effect occurs already within one chloroplast and the spectral distortion depends significantly on the excitation regime of the chloroplast. A theoretical dependence of the distortion function, defined as a change in the F(685)/F(735) fluorescence band ratio, on the mean chlorophyll concentration in a chloroplast is predicted for different light excitation regimes. The distortion of measured chlorophyll fluorescence spectra at 77 K of chloroplast suspension adsorbed on filter papers of two strongly different diffusive reflectivities and at different mean chlorophyll concentrations are discussed with the help of the presented theory.